2018
DOI: 10.1002/14651858.cd005974.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Homeopathic medicinal products for preventing and treating acute respiratory tract infections in children

Abstract: BackgroundAcute respiratory tract infections (ARTIs) are common and may lead to complications. Most children experience between three and six ARTIs annually. Although these infections are self-limiting, symptoms can be distressing. Many treatments are used to control symptoms and shorten illness duration. Most have minimal benefit and may lead to adverse e ects. Oral homeopathic medicinal products could play a role in childhood ARTI management if evidence for e ectiveness is established. ObjectivesTo assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 49 publications
(28 reference statements)
0
20
0
4
Order By: Relevance
“…Totally negative conclusions can be drawn for homeopathy. A recent Cochrane review that analyzed eight randomized controlled trials comparing oral homeopathy medicinal products with identical placebo or self-selected conventional treatments to prevent or treat acute RTIs in children aged 0 to 16 years supports this [ 29 ]. When the four studies regarding prevention were pooled, it was found that homeopathic medicinal products conferred no preventive effect on acute RTIs (OR 1.14, 95% CI 0.83–1.57) and were not associated with a reduction of the need for antibiotic usage (OR 0.79, 95% CI 0.35 to 1.76).…”
Section: Complementary and Alternative Medicinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Totally negative conclusions can be drawn for homeopathy. A recent Cochrane review that analyzed eight randomized controlled trials comparing oral homeopathy medicinal products with identical placebo or self-selected conventional treatments to prevent or treat acute RTIs in children aged 0 to 16 years supports this [ 29 ]. When the four studies regarding prevention were pooled, it was found that homeopathic medicinal products conferred no preventive effect on acute RTIs (OR 1.14, 95% CI 0.83–1.57) and were not associated with a reduction of the need for antibiotic usage (OR 0.79, 95% CI 0.35 to 1.76).…”
Section: Complementary and Alternative Medicinesmentioning
confidence: 99%
“…In recent years, based on evidence that in the first years of life the immune system is immature and partially unable to defend against infectious agents [ 18 ], the use of immunotherapy, i.e., measures that are able to stimulate and/or regulate the activity of some components of the immune system, thereby making host defenses more efficient, has been advocated [ 19 , 20 ]. Moreover, attempts to use vitamins [ 21 , 22 , 23 ], probiotics [ 24 , 25 , 26 , 27 ], oligo-elements [ 27 ], and complementary and alternative medicine [ 28 , 29 ] have been made. Unfortunately, the real benefits offered by some treatments are dubious, and they should be avoided until supported by evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Es gibt andere naturheilkundliche An-sätze, wie z.B. die Homöopathie [ 11 ], die Symbioselenkung [ 12 ], auch diverse Ansätze in der Ernährungsbera-tung [ 13 ], die erfahrungsgemäß bes-sere Erfolge bei Infektneigung und akuten Infekten haben.…”
Section: Was Tun?unclassified
“…Hawke et al 16 in their systematic review on ARTIs with the objective to assess the efficacy and safety of oral homeopathic medicinal products with placebo or conventional therapy to prevent and treat ARTIs in children aged 0 to 16 years evaluated eight RCTs. The results of the study found low-quality evidence for non-individualised and individualised homeopathic medicinal product to prevent ARTIs (odds ratio [OR]:…”
Section: Systematic Reviewsmentioning
confidence: 99%